Probing the non-thermal emission in the Perseus cluster with the JVLA. Issue Volume 14:Issue S342(2018) (May 2018) - Gendron-Marsolais, M.; Hlavacek-Larrondo, J.; van Weeren, R. J.; Clarke, T.; Fabian, A. C.; Intema, H. T.; Taylor, G. B.; Blundell, K. M.; Sanders, J. S.
Abstract: We present deep low radio frequency (230-470 MHz) observations from the Karl G. Jansky Very Large Array of the Perseus cluster, probing the non-thermal emission from the old particle population of the AGN outflows. Our observations of this nearby relaxed cool core cluster have revealed a multitude of new structures associated with the mini-halo, extending to hundreds of kpc in size. Its irregular morphology seems to have been influenced both by the AGN activity and by the sloshing motion of the cluster' gas. In addition, it has a filamentary structure similar to that seen in radio relics found in merging clusters. These results illustrate the high-quality images that can be obtained with the new JVLA at low radio-frequencies.